The Effect of Rest Between Sets on The Repetition of A Women's Bench Press (Universitas Negeri Semarang, 2022)
This study aims to determine the effect of the rest between sets on the number of repetition for bench press using power method in women. The method used is Poor Experimental with The One-Group Pretest-Posttest Design. The sample in this study were active students of Sport Science FPOK UPI with a total sample of 10 people. The sampling technique used purposive sampling. The instrument used was a free weight bench press to calculate the number of repetitions. The results of data analysis showed that there was an effect of rest s on the reduction in the number of repetition, at rest 2 minutes and 3 minutes, except at rest 5 minutes. K-Independent Samples test showed that there was a difference in the number of repetition in the second set in all rest. 2-Independent Samples test show that there is a difference in effect on the rest 2 minutes with 3 minutes and 2 minutes with 5 minutes, except at the rest 3 with 5 minutes. So, it can be concluded that there is an effect of the rest between sets of 2 minutes and 3 minutes on the number of repetition for bench press in women.